5-HT6 Receptor Antagonist as an Adjunct Treatment Targeting Residual Symptoms in Patients With Schizophrenia: Unexpected Sex-Related Effects (Double-Blind Placebo-Controlled Trial). Issue 2 (April 2017) - Morozova, Margarita; Burminskiy, Denis; Rupchev, George; Lepilkina, Taissia; Potanin, Sergey; Beniashvili, Allan; Lavrovsky, Yan; Vostokova, Natalia; Ivaschenko, Alexander
Abstract: Background: Treating patients who experience residual psychotic symptoms during remission of schizophrenia remains one of the most challenging problems. The mechanisms underlying these symptoms differ from those of acute hallucinations and delusions. 5-HT6 receptor antagonists have been considered promising agents in treatment of residual psychotic symptoms and cognitive dysfunction. The aim of the study was to assess the efficacy of a selective 5-HT6 inhibitor Avisetron in the reduction of residual psychotic symptoms in patients with schizophrenia on stable antipsychotic therapy. Methods: Eighty clinically stable outpatient subjects with schizophrenia with residual psychotic symptoms were randomized in a double-blind manner to 6 weeks of Avisetron or placebo at 1:1 ratio. Subjects received 8 mg of Avisetron or placebo on top their stable antipsychotic treatment. Standard clinical scales and cognitive tests were used for endpoint assessment. The primary efficacy endpoint was the mean reduction of total Positive and Negative Syndrome Scale score after 6 weeks of treatment. Results: No significant differences in the primary and secondary endpoints were found between the groups. However, based on the subgroup analysis, the significant improvement of total Positive and Negative Syndrome Scale score and residual psychotic symptoms was observed in female patients. Conclusions: It was a negative study with unexpected benefits of the drug only in females. We hypothesized that the role of patients' sex can impact the treatment response to serotonergic drugs in general. We suggest a possible synergistic interaction between estrogen and Avisetron by means of modulating the effect of estrogens on the serotonergic system. Future studies targeting the sex-related effects of serotonergic drugs are warranted.